Timeliness Value and Free-from-error Quality of Accounting Information: A Study on Commercial Banks - Ahamed, Mohammad Jafaur (Asian Business Review, 2020)
This paper makes an effort to assess the timeliness value and free-from-error quality of accounting information generated by AIS through the avenue of annual reports of the selected commercial banks in Bangladesh. An opinion survey was run through a closed questionnaire- designed by using a five-point Likert scale. Based on primary data, the study reveals that the qualities of accounting information produced by AIS of commercial banks are satisfactory in terms of both timeliness and free-from-error, yet inadequate in absolute terms. Moreover, the study substantiates that there is no significant variation (homogeneity) of opinion among the respondents regarding the timeliness and accuracy of accounting information. The outcomes of the study identified that the feature of annual reports of commercial banks in Bangladesh is not up to the standard due to erratic power supply, poor communication infrastructures, the accidental entry of poor data, virus infection, unauthorized accessing, copying, printing and distributing of data or information, etc. Consequently, respective authorities are highly encouraged to come forward to ensure the maximum qualities of AIS. The study has focused on two qualitative characteristics and only on the annual report. Thus, further research is recommended to conduct focusing on others such as quarterly and interim reports, bank circulars, financial press releases, etc. to investigate the extent of additional qualities, for instance, feedback value, credible value, clarity value, etc.